TRANSFORMATIONAL LEADERSHIP AND TOTAL QUALITY MANAGEMENT: HOW DOES IT AFFECTS EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE? - Yudhistira Pradhipta Aryoko; Rezky Pramurindra; Irawan Randikaparsa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to test whether Job Satisfaction is able to mediate the influence of Transformational Leadership and Total Quality Management (TQM) on Employee Performance. This study used a sample of 106 respondents. In this study, data analysis used the Partial Least Square (PLS) approach. PLS is a component-based Structural Equation Modeling (SEM). Based on the results of this study, several conclusions were found: Transformational Leadership (X1) has a positive and significant effect on Employee Performance (Y); Total Quality Management (X2) has a positive and significant effect on Employee Performance (Y); Transformational Leadership (X1) does not have significant effect on Job Satisfaction (Z); Total Quality Management (X2) has a positive and significant effect on Employee Performance (Y); Job Satisfaction (Z) has a positive and significant effect on Employee Performance (Y); Job Satisfaction (Z) could also mediate the relationship between Transformational Leadership (X1) and Total Quality Management (X2) on Employee Performance (Y).